Social capital strategies to enhance hepatitis C treatment awareness and uptake among men in prison. Issue 2 (24th October 2016) - Lafferty, L.; Treloar, C.; Guthrie, J.; Chambers, G. M.; Butler, T.
Summary: Prisoner populations are characterized by high rates of hepatitis C (HCV), up to thirty times that of the general population in Australia. Within Australian prisons, less than 1% of eligible inmates access treatment. Public health strategies informed by social capital could be important in addressing this inequality in access to HCV treatment. Twenty‐eight male inmates participated in qualitative interviews across three correctional centres in New South Wales, Australia. All participants had recently tested as HCV RNA positive or were receiving HCV treatment. Analysis was conducted with participants including men with experiences of HCV treatment (n=10) (including those currently accessing treatment and those with a history of treatment) and those who were treatment naïve (n=18). Social capital was a resourceful commodity for inmates considering and undergoing treatment while in custody. Inmates were a valuable resource for information regarding HCV treatment, including personal accounts and reassurance (bonding social capital), while nurses a resource for the provision of information and care (linking social capital). Although linking social capital between inmates and nurses appeared influential in HCV treatment access, there remained opportunities for increasing linking social capital within the prison setting (such as nurse‐led engagement within the prisons). Bonding and linking social capital can be valuable resources in promoting HCV treatment awareness, uptake and adherence. Peer‐based programmes are likely to be influential in promoting HCV outcomes in the prison setting. Engagement in prisons, outside of the clinics, would enhance opportunities for linking social capital to influence HCV treatment outcomes.